The Role of Decentralization in the Management of Natural-Recreational Potential of Territory - Myskovets Nаtalia P.; Skakovska Svitlana S. (Bìznes Inform, 2018)
The article is aimed at defining the main aspects of decentralization reform impacting the territory’s natural-recreational potential. The current status of implementation of the decentralization reform is characterized, the main priorities in the association of territorial communities are defined. The experience of Poland in the implementation of reform of decentralization is analyzed, the «Report on the status of gmina» is considered in detail, the most actual moments for assimilation of the experience in the Ukrainian united territorial communities are allocated, which will facilitate a rational use of the natural-recreational potential of territory with maximum capitalization. The authors have allocated the factors that influence the formation and functioning of united territorial communities. The changes in the tax and budget codes to increase the financial capacity in management of financial resources of united territorial communities, and more precisely the means of communities and enterprises, are displayed.